An Anthropometric Study of Stature Estimation from Foot Morphometry in North Indian Population (Medico Legal Update, 2020)
Background and Objectives: The aim of present study is to find the correlation of foot morphometry withstature and to derive the regression equation for stature estimation among two endogamous (baniya and jats)groups of North India.Material and Method: The present study was carried out at Department of Anatomy, MMIMSR Mullana–Ambala, on 400 subjects(100 males,100 females of each group) belonging to known endogamous group(baniya and jats) of Haryana, age group ranged between 21-35 years. Height and foot length,foot breadth wasmeasured. Foot index was calculated. Statistical analysis including mean, standard deviation for stature andfoot morphometry of both sides were calculated separately for both sexes. Pearson’s correlation coefficientwas calculated to find correlation between stature and different foot morphometry .To estimate stature fromfoot morphometry linear regression analysis was done.Results: The mean and standard deviation for height in males was 173.68 ± 7.336 and in females was160.73 ± 10.049 with highly significant p value. The mean foot length,foot breadth of males was higher thanfemales with statistically significant p value. In males, the foot length and foot breadth of both sides havea highly significant correlation with height. In females the correlation of height was highly significant withfoot length, foot breadth and foot index among both the groups.Conclusion: A significant correlation coefficient was observed between height and foot length in males. Infemales, a significant correlation was observed between height and foot length and foot breadth. If either ofthe measurement is known(height or foot length/foot breadth), the other can be calculated. This would beuseful for Anthropologists and Forensic medicine experts.